Contribution of Racial and Ethnic Differences in Cerebral Small Vessel Disease Subtype and Burden to Risk of Cerebral Hemorrhage Recurrence. (18th May 2021) - Castello, Juan Pablo; Pasi, Marco; Abramson, Jessica R.; Rodriguez-Torres, Axana; Marini, Sandro; Demel, Stacie; Gilkerson, Lee; Kubiszewski, Patryk; Charidimou, Andreas; Kourkoulis, Christina; DiPucchio, Zora; Schwab, Kristin; et al.
Abstract : Objective: Black and Hispanic survivors of intracerebral hemorrhage (ICH) are at higher risk of recurrent intracranial bleeding. MRI-based markers of chronic cerebral small vessel disease (CSVD) are consistently associated with recurrent ICH. We therefore sought to investigate whether racial/ethnic differences in MRI-defined CSVD subtype and severity contribute to disparities in ICH recurrence risk. Methods: We analyzed data from the Massachusetts General Hospital ICH study (n = 593) and the Ethnic/Racial Variations of Intracerebral Hemorrhage (ERICH) study (n = 329). Using CSVD markers derived from MRIs obtained within 90 days of index ICH, we classified ICH cases as cerebral amyloid angiopathy (CAA)–related, hypertensive arteriopathy (HTNA)–related, and mixed etiology. We quantified CSVD burden using validated global, CAA-specific, and HTNA-specific scores. We compared CSVD subtype and severity among White, Black, and Hispanic ICH survivors and investigated its association with ICH recurrence risk. Results: We analyzed data for 922 ICH survivors (655 White, 130 Black, 137 Hispanic). Minority ICH survivors had greater global CSVD ( p = 0.011) and HTNA burden ( p = 0.021) on MRI. Furthermore, minority survivors of HTNA-related and mixed-etiology ICH demonstrated higher HTNA burden, resulting in increased ICH recurrence risk (all p < 0.05). Conclusions: We uncovered significant differences in CSVD subtypes and severity among White and minority survivors of primary ICH, with direct implication for known disparities in ICH recurrence risk. Future studies of racial/ethnic disparities in ICH outcomes will benefit from including detailed MRI-based assessment of CSVD subtypes and severity and investigating social determinants of health.